Stratigraphic evolution and drowning steps of a submerged isolated carbonate platform in the northern South China Sea - Chen, Wanli; Wu, Shiguo; Wang, Dawei; Betzler, Christian; Ma, Yongsheng (Frontiers in Marine Science, 2023)
Drowned carbonate platforms on passive margins present a paradox because their great growth potential exceeds typical rates of passive margin subsidence and any relative rise of sea level driven by long-term processes in the geologic record. Here, the manned submersible observations and sampling as well as high-resolution acoustic data are used to investigate a drowned isolated carbonate platform cropping out at a water depth of 536-800 meters in the northern South China Sea. Our results show that the Early Miocene strata of the platform are grouped into 3 units (AU1, AU2, AU3) that formed on fault created topography. Faulting formed topography served as templates for the start of carbonate platform deposition and as pedestals for the localization of backstepped platforms in response to variations of accommodation space primarily driven by rapid subsidence and eustatic rises during the Early Miocene. The Middle Miocene strata of the platform are grouped into 4 units (AU4, PU1, PU2, PU3), exhibiting a general switch from dominantly aggrading to dominantly prograding platform margins hand in hand with the cessation of faulting. Biostratigraphy and established seismic-stratigraphic correlation indicate that the carbonate platform was submerged during the late Middle Miocene. The banktop consists of a heterozoan carbonate factory dominated by large benthic foraminifera and coralline algae. This facies was deposited during a time interval when summer monsoon-induced upwelling triggered heterozoan factory turnovers in other carbonate platforms in the region, such as in well XK-1(Xisha Platform). The asymmetric backstepping of platform margins demonstrates that summer monsoon-driven currents influenced the drowning of the platform. Therefore, summer monsoon-induced upwelling is a major factor to be taken into consideration for the platform drowning during the late Miocene. The high subsidence rate throughout the Late Miocene made the platform growth fail to persist. This study provides new insight into drowning mechanism of a Miocene carbonate platform in the northern South China Sea, and provides a new seismic analog for other ancient isolated platforms worldwide.